Türkiye’de Türkçenin ve İngilizcenin yabancı dil olarak öğretilmesinde ve öğrenilmesinde ders kitabının rolü: Bir vaka çalışması - Pilica, Bisera (My University, 2005)
The Role of the Foreign Language Coursebook in Teaching and Learning of English and Turkish as a Foreign Language in Turkey: A Case study by Bisera Pilica The present study aims to investigate the role of English and Turkish coursebooks as a foreign language teaching and learning tool in Turkey. It is to be noted that, in this study, English is the non-native language while Turkish is the native one in Turkey. Therefore, English is considered as a foreign language to be taught to Turkish native learners and Turkish is considered as a foreign language to be taught to foreign learners in Turkey. In this case, Turkish is taken to be a foreign language, although it is the native tongue in Turkey. This research was conducted at the Istanbul branch of TÖMER, (the Turkish and Foreign Language Research and Application Centre of Ankara University) during the 2003-2004 academic year. The study followed the learning and teaching processes of two English and Turkish classes from the 'Beginner 1' level to the 'Intermediate 1' level. Levels are determined as a result of a placement examination taken at TÖMER. Throughout the 2003 - 2004 academic year, an observation session was held once a month in both groups six times in total. An interview was held with randomly selected learners from each group throughout the course. At the end of the course an interview was held with the teachers, as xiv well. Therefore it was achieved to be interviewed all learners and teachers in the end. A questionnaire was also administered to both learners and teachers at the end of the course. The two major questions of the research are shown below: 1. What is the role of the English coursebook as a foreign language teaching and learning material in Turkey? 2. What is the role of the Turkish coursebook as a foreign language teaching and learning material in Turkey? The study has six sub-questions, as indicated below: 1. To what extent do teachers and learners depend on the English coursebook as a foreign language teaching and learning material in Turkey? 2. To what extent do teachers and learners depend on the Turkish coursebook as a foreign language teaching and learning material in Turkey? 3. How does being a non-native English speaker affect Turkish teachers while using the English coursebook and giving English language instruction in English classes in Turkey? 4. How does being a Turkish native speaker affect teachers while using the Turkish coursebook and giving Turkish language instruction in Turkish classes in Turkey? 5. What is the importance of the relationship between the environment and the coursebook while teaching and learning English as a foreign language in Turkey? 6. What is the importance of the relationship between the environment and the coursebook while teaching and learning Turkish as a foreign language in Turkey? The results indicated that the role of the coursebook is very significant in non-native language teaching and learning setting. The foreign language coursebook was exploited more extensively as the main aid by the learners and the non-native speaker teachers in the non-native language setting than the coursebook users who were in the native language setting. The results very clearly stated that the group of learners and non-native speaker teachers in their non-native xv language setting needed their language coursebooks more than the learners and native speaker teachers in their native language setting. It was obtained in this study that non-native language teachers in the non-native language setting relied on the coursebook more than the native language teacher in their native language setting. For that reason the non-native language teachers depended on the coursebook and used it more thoroughly while the native language teachers used the coursebook as an aid. As the last finding, since there is no desired contribution from the immediate environment, considering particularly Turkey, therefore, the language coursebook was used as the main aid for both learning and teaching in the non-native language setting. Conversely, the fact of learning a foreign language in its native country offers a surplus of input from the environment and therefore the native language setting group benefited from the environment a great deal. xvi

Türkiye'de Türkçenin ve İngilizcenin Yabanci Dil Olarak Öğretilmesinde ve Öğrenilmesinde Ders Kitabının Rolü: Bir Vaka Çalışması Bisera Pilica Bu çalışmanın amacı, Türkiye'de İngilizce ve Türkçe ders kitaplarının bir yabancı dil öğretim ve öğrenim aracı olarak rolünü araştırmaktır. Araştırma, TÖMER (Türkçe ve Yabancı Dil Araştırma ve Uygulama Merkezi) İstanbul şubesinde yapılmıştır. Çalışma TÖMER'deki 'Başlangıç Düzeyi 1' ve 'Orta Düzeyi 1' gruplarında gerçekleştirilmiştir. Sınıf seviyeleri kurum tarafından yapılan yerleştirme sınavının sonuçlarına göre belirlenmektedir. Çalışma için gerekli olan veriler, İngilizce sınıfına devam eden 7, Türkçe sınıfına devam eden 6 öğrenciden elde edilmistir. 2003 -2004 akademik yılı boyunca her iki grupta ayda 1 kez olmak üzere toplam 6 kez gözlem yapılmıştır. Araştırma boyunca her iki gruptan rastgele seçilmiş öğrencilerle söyleşi gerçekleştirilmiştir. Kursun sonunda öğretmenlerle de birer söyleşi yapılmıştır. Çalışmanın sonunda tüm öğrenci ve öğretmenlerle söyleşi uygulaması gerçekleştirilmiştir. Orta düzey kurunun sonunda hem öğrencilere hem de öğretmenlere birer adet davranış anketi de uygulanmıştır. xvii Araştirma aşagidaki temel sorulara cevap aramıştır: 1. Türkiye'de İngilizcenin yabancı dil olarak öğretilmesinde ve öğrenilmesinde İngilizce ders kitabının rolü nedir? 2. Türkiye'de ana dilin, yabancı dil olarak öğretilmesinde ve öğrenilmesinde Türkçe ders kitabının rolü nedir? Çalışmada iki temel sorunun yanısıra altı alt soru aşağıdaki gibi düzenlenmiştir. 1. Türkiye'de İngilizcenin yabancı dil olarak öğretilmesinde ve öğrenilmesinde öğretmenler ve öğrenciler ders kitaplarına ne derece bağlı-bağımlı çalışmaktadırlar? 2. Türkiye'de Türkçenin yabancı dil olarak öğretilmesinde ve öğrenilmesinde öğretmenler ve öğrenciler ders kitaplarına ne derece bağlı-bağımlı çalışmaktadırlar. 3. Ana dilinin İngilizce olmaması, İngilizceyi yabancı dil olarak öğreten ve İngilizce ders kitabı kullanan, ana dili Türkçe olan, İngilizce öğretmenlerini nasıl etkilemektedir? 4. Ana dilinin Türkçe olması, Türkçeyi yabancı dil olarak öğreten ve Türkçe ders kitabı kullanan Türkçe öğretmenlerini nasıl etkilemektedir? 5. İngilizcenin Türkiye'de yabancı dil olarak öğretilmesi ve öğrenilmesinde çevre ve yabancı dil ders kitabının arasındaki ilişkinin önemi nedir? 6. Türkçenin Türkiye'de yabancı dil olarak öğretilmesi ve öğrenilmesinde çevre ve yabancı dil ders kitabının arasındaki ilişkinin önemi nedir? Elde edilen bulgulara göre, Türkiye'de İngilizcenin yabancı dil olarak öğretilmesinde İngilizce ders kitabının ana araç olarak kullanılması nedeniyle çok etkin olduğu görüldü. Türkiye'de ana dilin yabancı dil olarak öğretilmesinde kullanılan Türkçe ders kitabının, Türkiye'de İngilizcenin yabancı dil olarak öğretilmesinde kullanılan İngilizce ders kitabına kıyasla daha az etkin olduğu görüldü. xviii Türkiye'de Türkçenin yabancı dil olarak öğretilmesinde, öğretmenler ve öğrencilerin ders kitaplarına Türk İngilizce öğretmenleri ve öğrencileri kadar bağımlı olmadıkları izlendi. Türkiye'de İngilizcenin yabancı dil olarak öğretilmesinde, öğretmenler ve öğrencilerin ders kitaplarına, en temel araç olarak kullanılması nedeniyle ileri derecede bağımlı oldukları gözlendi. Araştırma, Türkiye'de Türkçenin yabancı dil olarak öğretilmesinde ders kitabı-bağlam-ortam ilişkisinin de çok önemli olduğunu ortaya çıkardı. Türkiye'de İngilizcenin yabancı dil olarak öğretilmesinde ders kitabı-bağlam-ortam ilişkisinin aynı derecede güçlü olmadığı gözlemi de araştırmanın diğer önemli bulguların arasındadır.
Keywords: Dil ve Diller_Öğrenim ve Öğretim